Photodegradation of atrazine in the presence of indole-3-acetic acid and natural montmorillonite clay minerals. (September 2018) - Zhang, Lin; Tian, Haoting; Hong, Ran; Wang, Chao; Wang, Yi; Peng, Anping; Gu, Cheng
Abstract: Atrazine (2-chloro-4-ethylamino-6-isopropylamino-s-triazine) is a commonly used agricultural herbicide that, as a result, is frequently detected in surface and ground water. In this study, we provide evidence of the photo-oxidation of atrazine under environmentally relevant conditions, specifically, in the presence of natural montmorillonite clay and the ubiquitous phytohormone indole-3-acetic acid (IAA). The reaction is initiated by the generation of hydrated electrons from the photo-ionization of IAA. These electrons react with protons and dissolved oxygen to form hydroxyl radicals, which promote the further degradation of atrazine. Montmorillonite strongly enhances the yield of hydrated electrons and prolongs their lifetime, by stabilizing radical cations through electrostatic attraction by the negative charges embedded in the clay. Moreover, by providing a confined space, montmorillonite markedly increases the probability of contact between atrazine and the active radicals. Other factors strongly influencing the degradation process are the solution pH, the type of exchangeable cations present in the clay interlayer, and the hydration status of montmorillonite. Since both IAA and montmorillonite clay are widely distributed in the environment, the proposed reaction is predicted to play an important role in the degradation of atrazine and perhaps other potentially persistent organic contaminants. Graphical abstract: Image 1 Highlights: Atrazine is photooxidized in presence of IAA and MMT at environmental condition. OH is responsible for the degradation process. Montmorillonite can greatly enhance this process. This process is affected by pH, exchangeable ion and hydration status of MMT. Abstract : Atrazine is photo-oxidized in the presence of indole-3-acetic acid and montmorillonite under environmentally relevant condition. Montmorillonite enhances the process.